O impacto do empobrecimento na velhice - Salviano, Ednéia (2008)
Research focusing on the elderly population shows that one of the several fears associated with aging is fear of economic dependence. In light of this scenario and in view of the lack of specific studies on this theme, I became interested in investigating the impact that impoverishment had on the aging process of elderly individuals who had a good financial situation throughout their life. To achieve this, a qualitative research was developed in which six people (two men and four women) between the ages of 59 and 82 were interviewed. These individuals used to be rich and, due to some event, became impoverished in old age. The hypothesis that guided the study was that these subjects denied that possibility during their entire life and did not think of protecting themselves financially; this fact aggravated the impact they suffered due to the negative life event. The collected data allowed me to conclude that the impact of impoverishment on elderly individuals who used to have a good financial situation was felt with less or more intensity depending on the type of life trajectory constructed by each subject. Those who cultivated a social network supported by multiple axes showed greater capacity to adapt to stressful events deriving from changes in their project of life and seem to have greater facility to accept and assimilate life s lessons, reinventing themselves